Formulasi Sediaan Gummy Candies Analgetic Kombinasi Ekstrak Daun Pepaya (Carica papaya L.) Dan Daun Kelor (Moringa oleifera lam.) - Arifina Fahamsya; Endang Istriningsih; Novita, Salsa Adinda (STIKes Ibnu Sina Ajibarang, 2024)
Analgesics are drugs that selectively reduce pain by acting in the central nervous system or on peripheral pain mechanisms, without altering consciousness. The types of plants used in medicine are papaya leaves and moringa leaves. Papaya leaves and Moringa leaves contain secondary metabolite compounds; one of them is flavonoids that act as analgesics. The purpose of this study was to determine the combination of papaya leaf extract and Moringa leaves made into gummy candies, to find out the best formulation of the gummy candies. The method in this study was the experimental method. The type of extraction in this study using 70% alcohol solvent. The extract was formulated into gummy candies and conducted evaluation tests including organoleptic, weight uniformity, pH, chewiness, and favorability tests. The organoleptic test results showed that all formulations had a distinctive aroma of brown essence and chewy texture, while the color of formulation 0 was clear yellow. Formulation 1, 2, and 3 were dark brown. Weight uniformity test on all four formulations was no deviated weights. The pH tests of all formulations had the same pH of 6 meaning that met the pH requirements with a range of 5-7. Chewiness tests on all formulations had a range of 4 cm. The condition for the elasticity of gummy candies was that the longer they were, the chewier they were. The results of the hedonic test or favorability test were analyzed using the Kruskal wallis test of each parameter of interest, namely formulation color 0, aroma formulation 1, taste formulation 0, as well as texture formulation 0 and 1.